MOTOR DEVELOPMENT AND GAIT OF CHILDREN WITH OSTEOGENESIS IMPERFECTA: LITERATURE REVIEW - Guedes da Silva, Keyte; Silva Vilas Boas Pereira, Karine; da Silva Rodrigues, Gisele (Health and Society, 2023)
For hereditary reasons, an individual can develop a deficit in the COL1A1 and COL1A2 genes, resulting in a lack of collagen and causing imperfect osteogenesis. Thus, this work aimed to present a literature review that addressed the motor development and gait of individuals with carriers, analyzing the interventions and treatments that bring positive benefits by improving motor function. The research was carried out in the bibliographic databases Pubmed, PMC Central, Scielo, PeDro, Crochrane, Reaserach Gate and Lilacs, selecting articles published in English and Portuguese between the period 2011 to 2020. The bibliographic survey took place between February and November 2021. 21 articles were included in the study according to the established criteria. In conclusion, it was observed that the physiotherapeutic intervention is effective and brings benefits, minimizing the impacts on the motor development of individuals with osteogenesis imperfecta, providing an improvement in the quality of life in children with osteogenesis imperfecta.